Multi-agent Description of a Complex Object Based on Certain Information - Косовская, Татьяна Матвеевна (Computer Tools in Education, 2017)
Three problems of an object description based on certain incomplete information received by several agents are under consideration. An object in the first problem is characterized by global binary features and is described by a string of these features values. An object in the second and in the third problems is presented as a set of its elements and is characterized by properties of these elements and relations between them. It is described by a set of constant atomic predicate formulas. It is supposed that all agents in the second problem have the same name for every object element. In the third problem every agent does not know the true names of the object elements and arbitrarily gives names for them. Algorithms solving the set problems are described and the upper bounds of these algorithms run steps are proved. Model examples of an algorithm implementation are given for the second and the third problems.